Studi Kasus Kebocoran Fuel di Area Fuel Drains Tank Ejector pada Mesin Pesawat Airbus A330-300 - James Siregar; Lalu Giat Juangsa Putra; Muhammad Andi Nova; Mohamad Alif Dzulfiqar; Nur Rafia Dija; Tsabita Salmahirah; Rizky Pratama Hudhajanto (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2026)
Fuel leaks in aircraft engines are a critical maintenance issue that can compromise flight safety and increase operating costs. This study aims to analyze the causes and resolve a specific case of a fuel leak classified as a stain (wet area diameter less than ¾ inch) on the fuel drains tank ejector area of the right engine (Engine 2) of an Airbus A330-300 PK-GHC aircraft. The methodology employed includes visual field observations and a review of technical documents based on Aircraft Maintenance Manual (AMM) 71-71-00-200-802-A and Troubleshooting Manual (TSM) task card 71-71-42-000-804-A. The investigation results showed that the leak was caused by structural damage to the left input connector. Corrective action was successfully executed by replacing the connector and installing a new seal ring (Part Number AS43013-131), followed by tightening the bolts to a torque specification of 90–110 lbf.in and the connector to 193.5–236.5 lbf.in. A post installation visual check confirmed that the system returned to normal operation with zero subsequent leaks. This case study provides a practical contribution by establishing that the connector on the fuel drains tank ejector is a critical component requiring regular preventive inspections, serving as a technical reference to prevent similar potential leak risks on wide-body aircraft fleets.